2017
DOI: 10.1002/aoc.3824
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazine based Pt(II) bis‐alkynyl organometallic complexes: Synthesis, characterization, and cytotoxic effect on A549 human lung carcinoma cells

Abstract: A facile and efficient synthesis of a series of five new pyrazine-based organometallic complexes is being reported. The complexes (2-6) have been fully characterized.Molecules 2, 3 and 6 were structurally characterized by single crystal X-ray crystallographic analyses. Additionally, anticancer properties of these organometallic complexes have been studied against A549 human lung carcinoma cells. Biological studies suggest that complex 5 (with pendant pyridine moieties) exhibited maximal growth inhibitory cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…In a recent study, good antiproliferative ability of Au­(I) complexes was coupled with excellent photophysical properties of Re complexes to generate hybrid probes with new properties and application . Other than these examples, several organic and organometallic complexes endowed with anticancer, antibacterial, antifungal, and for cellular component or protein imaging , and photodynamic therapy are available.…”
Section: Applicationsmentioning
confidence: 99%
“…In a recent study, good antiproliferative ability of Au­(I) complexes was coupled with excellent photophysical properties of Re complexes to generate hybrid probes with new properties and application . Other than these examples, several organic and organometallic complexes endowed with anticancer, antibacterial, antifungal, and for cellular component or protein imaging , and photodynamic therapy are available.…”
Section: Applicationsmentioning
confidence: 99%
“…In particular, a considerable effort is being devoted toward the development of organometallic compounds with antitumor activity. , The library of organometallic species with antiproliferative activities has seen marked growth in recent years with reports on organometallic compounds. Among the transition metals, organometallic compounds of ruthenium , and gold , have been studied most extensively as antitumor agents. On the other hand, reports on Pt­(II)-based organometallics in the same context are relatively less in number. Most of the reported organoplatinum­(II) compounds have an exchangeable and labile alkene ligand (1,5-cyclooctadiene) bound to the Pt­(II) center. Additionally, there are some examples of cyclometalated organometallic complexes of Pt­(II) that are reportedly biologically active and are potential anticancer agents …”
Section: Introductionmentioning
confidence: 99%
“…In one of the very few examples, Najajreh et al reported trans -platinum complexes with piperidinopiperidine ligands that showed higher IC 50 values (less potent/cytotoxic) in A2780 cells relative to cisplatin . Similarly, Bhowmick et al reported a series of organometallic compounds with trans geometry at the Pt­(II) center having IC 50 values that are higher than or comparable to those of cisplatin. Cytotoxicity of organoplatinum molecules with alkynyl ligands was also reported by Klein and co-workers …”
Section: Introductionmentioning
confidence: 99%
“…Das and coworkers reported the first pyrazine based dialkynyl platinum derivatives that have been tested as anticancer agents. 90 Thus, a pyrazine ring was used as a bridge ligand between two platinum phosphane alkynyl unis at C2 and C6 positions. Then, each platinum center was covalently linked to an aromatic or heteroaromatic alkynyl derivative and two triethylphosphane ligands, affording robust complexes (98-102, see Fig.…”
Section: Dinuclear Alkynyl Platinum Complexesmentioning
confidence: 99%